Palynofacies analysis of Ida-4 well, Niger Delta Basin, Nigeria - Chukwuma-Orji, Jacinta Nkiru; Okosun, Edward Agboneni; Gana, Funmilayo Daramola (Geology, Geophysics and Environment, 2019)
Palynofacies analyses of the strata penetrated by Ida-4 wells were carried out with the aim of studying the stratigraphic sequence penetrated by the well in order to establish palynostratigraphic zones, relative age and the paleoenvironment of deposition. Fifty ditch cutting samples within the interval of 2179–3523 m were analyzed. The acid methods of sample preparation for palynofacies analyses were followed. The result of the analyses yielded low to abundant occurrences of pollen and spores with an abundance of small, medium and large sizes of palynomacerals 1 and 2, few occurrences of palynomacerals 3 and 4. The lithology consists of the alternation of shale and sandstone units with few intercalations of argillaceous sandstone units, indicating that the studied interval belongs to the Agbada Formation. The studied intervals were dated to the middle Miocene to late Miocene, based on the recovered age diagnostic marker species such as Zonocostatites ramonae, Multiareolites formosus, Verrutricolporites rotundiporus, Crassoretitriletes vanraadshoveni and Racemonocolpites hians. Two interval range palynostratigraphic zones: Multiareolites formosus – Zonocostatites ramonae, Verrutricolporites rotundiporus – Crassoretitriletes vanraadshoveni and a taxon range zone: Ainipollinite verus zone were proposed. Paleoenvironmental interpretation was based on the palynofacies association and the lithology which revealed that the stratigraphic interval studied was deposited in the Coastal-deltaic (marginal marine) environments.